Nusinersen for SMA: expanded access programme. Issue 9 (16th March 2018) - Farrar, Michelle A; Teoh, Hooi Ling; Carey, Kate A; Cairns, Anita; Forbes, Robin; Herbert, Karen; Holland, Sandra; Jones, Kristi J; Menezes, Manoj P; Morrison, Margot; Munro, Kate; Villano, Daniella; et al.
Abstract : Background: Spinal muscular atrophy (SMA) is a devastating motor neuron disorder causing progressive muscle weakness and respiratory insufficiency. We present the initial Australian experiences implementing the expanded access programme (EAP) to enable preapproval access to nusinersen, the first disease-modifying therapy, for SMA type 1. Methods: An Australian multicentre, open-label EAP for nusinersen enrolled patients with infantile-onset SMA type 1 from November 2016 to September 2017. Standard-of-care medical therapy and treatment with intrathecal nusinersen were provided to all patients. Clinical and diagnostic characteristics, molecular genetics, treatment administered, and functional motor outcomes were assessed. Results: A total of 20 patients with SMA type 1 met the inclusion criteria, of whom 16 consented and received nusinersen treatment. Median time to diagnosis from symptom onset was 5.0 months and was correlated with age of onset (r=0.54, P<0.05). Management shifts included proactive nutritional and pulmonary support in all newly diagnosed patients with increased complexity of decision making. Supplemental nutrition with or without nocturnal non-invasive ventilation was implemented during follow-up in new diagnoses with age of onset <3 months and 2 SMN2 copies. Conclusions: The nusinersen EAP highlights difficulties in achieving early diagnosis and/or prevention, the evolution of optimal clinical care in a time of uncertain prognostication, resource implications and ethical issues in clinical practice for SMA type 1. These challenges are broadly relevant to the realisation of all novel therapeutics in neurological disorders.